4-5 gadīgu bērnu sadarbības prasmju veicināšana rotaļā - Putniņa, Elīna (Latvijas Universitāte, 2021)
Bakalaura darba autors: Elīna Putniņa Bakalaura darba temats: „4-5 gadīgu bērnu sadarbības prasmju veicināšana rotaļā”. Mērķis: Teorētiski un empīriski pētīt rotaļu nozīmi 4-5 gadus vecu bērnu sadarbības prasmju veicināšanā. Darba pirmajā nodaļā tiek analizēta saskarsmes būtība, izstrādāts 4-5gadu vecu bērnu raksturojums temata ietvaros. Šajā nodaļā tiek aprakstīts, kā veidojas sadarbības prasmes pirmsskolā. Otrajā nodaļā pētīta rotaļu nozīme sadarbības prasmju veidošanā. Tiek noskaidrota rotaļu nozīme bērna personības attīstībā, aplūkoti rotaļu veidi un tas, kā sadarbības prasmes pilnveidojas rotaļā. Trešajā nodaļā tika veikts empīriskais pētījums par sadarbības prasmju veicināšanu rotaļā. Izvērtēts bērnu sadarbības prasmju līmenis pētījuma sākumā, izstrādāts un praksē pārbaudīts rotaļu kopums sadarbības prasmju pilnveidošanai. Tiek pārbaudītas un analizētas bērnu sadarbības prasmes pētījuma beigās. Empīriskajā daļā apstiprinājās hipotēze - rotaļa sekmē sadarbības prasmju attīstību, ja tā tiek izvēlēta atbilstoši bērnu vecumam un tās darbības paredz rotaļu dalībnieku sadarbību komandā. Atslēgas vārdi: sadarbība, sadarbības prasmes, bērna personība, rotaļa, Bakalaura darbs sastāv no 61 lappusēm, t.sk. – 3 tabulas, 6 attēli, 2 pielikumi. Izmantoti 50 informācijas avoti.

Bachelor`s Thesis paper` author: Elina Putnina Bachelor`s Thesis papers` issue: Cooperation skills promotion of 4-5 years old children by games. Main goal: Theoretically and practically research importance of collaboration skill promotion of 4-5-year-old children in child`s play and how to develop these skills. In papers first section the author analyses the meaning of collaboration, development of 4-5-year-old children`s characterization is being explained. This section talks about how collaboration skills develop in the kindergarten. In Second section research was done on the meaning of child`s play and collaboration skill development. The meaning of child`s play and how it affects child’s personal development was researched, many ways of child`s play was inspected and how collaboration skills develop through these processes. In third section practical research was done on collaboration skill promotion through child`s play. In the beginning of the research collaboration skill level was evaluated. An aggregate of child`s play on how to improve collaboration skills was developed and tested practically. Child`s collaboration skills were tested and analysed in the end of the research. Hypothesis approved in practical research, if one takes all the terms and conditions in mind that child`s play improves collaboration skills, if it is age proper and it anticipates plays group to collaborate in a team manner. Key words: collaboration, collaboration skills, child`s personality, child`s play. Bachelor paper consists of 61 pages, including 3 tables, 6 pictures, 2 addendums (added in addendum). Used 50 bibliography units.
Cooperation skills promotion of 4-5 years old children by games
Keywords: Skolas pedagoģija; sadarbība; sadarbības prasmes; bērna personība; rotaļa